A TIPS scorecard: Are TIPS accomplishing what they were supposed to accomplish? Can they be improved? - Michelle L. Barnes; Zvi Bodie; Robert K. Triest; J. Christina Wang (Federal Reserve Bank of Boston, 2009)
In September 1997, the U.S. Treasury developed the TIPS market in order to achieve three important policy objectives: (1) to provide consumers with a class of assets that allows for hedging against real interest rate risk, (2) to provide holders of nominal contracts a means of hedging against inflation risk, and (3) to provide everyone with a reliable indicator of the term structure of expected inflation. This paper evaluates progress toward the achievement of these objectives and analyzes prospective ways to better meet these objectives in the future, by, for example, extending the maturity of TIPS and/or the use of inflation indexes suited to particular geographic regions or demographics. We conclude by arguing that while it is tempting to consider completing markets by introducing more TIPS-like securities indexed to inflation rates more tailored to particular demographics, our analysis suggests that TIPS indexed to CPI do, in fact, facilitate good synthetic hedges against unexpected changes in inflation for many different investors, since the various inflation measures are very highly correlated. We do, however, argue for extending the maturity of TIPS.
Keywords: G10; G11; G18; 330